IMPLEMENTASI PENDIDIKAN AFEKTIF DALAM PEMBENTUKAN AKHLAK MULIA - Oktaviani Umayah (Jurusan PGMI FTIK IAIN Metro Lampung, 2017)
This research uses qualitative approach with case study. Data collection technique is done by (1) depth interview, (2) participant observation, and (3) documentation. Data were analyzed by interactive model consisting of data collection, data reduction, data display and conclusion. Validity checking is done with credibility test, transferability, dependability, and confirmability. The formation of noble character through the application of affective education that is represented in attitudes, attitudes, and gentle attitudes there is convincing evidence can have positive implications for the increase in awareness of worship, academic achievement, and the laudable behavior of learners in elementary education. Attentiveness creates an atmosphere of learning directed, controlled and measurable. The activity of the teacher's soul is focused on the condition of the learners to be understood, understood, evaluated and improved and optimized for their potential, and supported by the attitude of affection which creates a warm learning atmosphere and harmony in communicating between teachers and learners. The activity of the soul of the teacher who respects, loves, recognizes and upholds the existence of the learners is reflected in his attitude of a loving and loving parent towards his child and equipped with gentle attitude in creating a comfortable learning atmosphere (learning is fun), happy, passionate and fresh. The humanist, democratic and integrating human soul activity is reflected in its gentle, attractive, warm, empathetic, earthy, selfish, arrogant and authoritarian manner.